PENINGKATAN KEMAMPUAN PRAKTEK VIDEO TESTIMONI PROMOSI PRODUK UMKM BAGI GKS KEC. TEMBALANG - Ayu Febriana, kharisma; Nurwahyu Julianto, Edi; Manuhoro Setyowati, Retno (Universitas Semarang, 2021)
The advancement of information and communication technology is currently developing very rapidly, as well as in the world of MSMEs, one of which is for GKS Tembalang District, which requires the ability to practice video testimonials to promote their UMKM products to create competent human resources in their fields. requires theoretical and technical understanding through direct practice in making video testimonials, related to its UMKM products. The dedication with the title